A teamwork promotion of formin-mediated actin nucleation by Bud6 and Aip5 in Saccharomyces cerevisiae - Xie, Ying (2022)
Actin nucleation is achieved by collaborative teamwork of actin nucleator factors (NFs) and nucleation-promoting factors (NPFs) into functional protein complexes. Selective inter- and intramolecular interactions between the nucleation complex constituents enable diverse modes of complex assembly in initiating actin polymerization on demand. Budding yeast has two formins, Bni1 and Bnr1, which are teamed up with different NPFs. However, the selective pairing between formin NFs and NPFs into the nucleation core for actin polymerization is not completely understood. By examining the functions and interactions of NPFs and NFs via biochemistry, genetics, and mathematical modeling approaches, we found that two NPFs, Aip5 and Bud6, showed joint teamwork effort with Bni1 and Bnr1, respectively, by interacting with the C-terminal intrinsically disordered region (IDR) of formin, in which two NPFs work together to promote formin-mediated actin nucleation. Although the C-terminal IDRs of Bni1 and Bnr1 are distinct in length, each formin IDR orchestrates the recruitment of Bud6 and Aip5 cooperatively by different positioning strategies to form a functional complex. Our study demonstrated the dynamic assembly of the actin nucleation complex by recruiting multiple partners in budding yeast, which may be a general feature for effective actin nucleation by formins.